2006
DOI: 10.1007/s00026-006-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic Properties of Overpartitions into Odd Parts

Abstract: Abstract. In this article, we consider various arithmetic properties of the function p o (n) which denotes the number of overpartitions of n using only odd parts. This function has arisen in a number of recent papers, but in contexts which are very different from overpartitions. We prove a number of arithmetic results including several Ramanujan-like congruences satisfied by p o (n) and some easily-stated characterizations of p o (n) modulo small powers of two. For example, it is proven that, for n ≥ 1, p o (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 12 publications
1
58
0
Order By: Relevance
“…The generating function for po(n) is given by Many mathematicians have extensively studied the arithmetic properties of po(n) and they have also established several Ramanujan-type congruences satisfied by po(n) (for example, one can see [4,7]). Let A (n) denote the number of -regular overpartitions of n. The generating function for A (n) is given by…”
Section: N=1mentioning
confidence: 99%
“…The generating function for po(n) is given by Many mathematicians have extensively studied the arithmetic properties of po(n) and they have also established several Ramanujan-type congruences satisfied by po(n) (for example, one can see [4,7]). Let A (n) denote the number of -regular overpartitions of n. The generating function for A (n) is given by…”
Section: N=1mentioning
confidence: 99%
“…By employing dissection formulas, Fortin, Jacob and Mathieu [7], Hirschhorn and Sellers [9] independently derived various Ramanujan-type congruences for p(n), such as…”
Section: Introductionmentioning
confidence: 99%
“…Employing the 2-dissection formulas of theta functions due to Ramanujan, Hirschhorn and Sellers [9], Chen and Xia [4] obtained a generating function of p(40n + 35) modulo 5. Using the (p, k)-parametrization of theta functions given by Alaca, Alaca and Williams [1], they showed that…”
Section: Introductionmentioning
confidence: 99%
“…As the topic of overpartitions has already been examined rather thoroughly [3,4,5,6,7,8,10,11], we look to new constructions. One such construction is that of an overpartition pair of a positive integer n, defined by Lovejoy [9] as a pair of overpartitions wherein the sum of all listed parts is n. For example, the overpartition pairs of 2 are Lovejoy denoted the number of overpartition pairs of a positive integer n by pp(n), with pp(0) = 1 by definition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the following were proven in [7]. Also, Hirschhorn and Sellers [6] proved that p(n) satisfies congruences modulo non-powers of 2 by proving the following:…”
Section: Introductionmentioning
confidence: 99%